REKONTRUKSI MODEL KOLB LEARNING STYLE INVENTORY (KLSI) 4.0 BERBASIS MAQASHID SYARI’AH UNTUK GURU SEKOLAH DASAR FASE A - Marwan, Bairanti Asriandhini; Abas Mansur Tamam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to reconstruct an experiential learning model by integrating Kolb Learning Style Inventory (KLSI) 4.0, Islamic Experiential Learning Model (Brifkani, 2023), and Maqasid Syariah. The study addresses the limitations of conventional experiential learning models, which predominantly focus on cognitive aspects without explicitly incorporating spirituality. By linking Qur’anic tadabbur, tafakkur, tauhid concepts, and amal saleh, this model seeks to ensure that learning not only strengthens critical thinking skills but also fosters Islamic character development, particularly for Phase A students (ages 6-9). This research adopts a qualitative library research methodology, employing critical analysis and conceptual synthesis. The findings indicate that the proposed model provides a holistic approach that harmonizes cognitive, moral, and spiritual dimensions in education. The study recommends further evaluation through practical implementation in educational settings to assess its effectiveness in enhancing religious understanding, moral awareness, and social skills. Additionally, a systematic assessment framework is needed to measure the long-term impact of Maqasid Syariah integration in experiential learning on Islamic character formation.